IMPLEMENTING ETHNIC TOURISM AS A TOOL CONTRIBUTING TO THE DESTINATION COMMUNITY WELL-BEING IN THE CENTRAL HIGHLANDS, VIETNAM - Nguyen, Thi Thanh Kieu (Trường Đại học Đà Lạt, 2024)
Despite being well-recognized as a means of poverty alleviation in poor remote areas, ethnic tourism should not be solely pursued for economic benefits as an end goal for the host community. To achieve sustainability and destination community well-being, it is argued that ethnic tourism can become a tool to improve various types of community capital rather than only economic capital. The main goal of this study is to identify strategies to improve community capital in an ethnic tourism destination. By conducting a community workshop with 34 local tourism stakeholders in the Central Highlands, the study found that the top priority was placed on human capital and political capital. First, local wisdom and genuine characteristics of naivete, honesty, friendliness, and hospitality need to be promoted to attract visitors, while local residents need to be educated and trained to build capacity for improving tourism services and to actively engage in the tourism decision-making process. Second, improvements in political capital were strongly suggested to tackle common barriers to community empowerment and collaboration, tourism organizational structure, local policies, standards, and assessment procedures. This study reaffirms the interrelationship and synergy among types of community capital and proves the value of the destination community well-being approach to ethnic tourism planning and governance. Future research implications are also presented.